Endocytic internalization routes required for Delta/Notch signaling - Windler, Sarah L. (2010)
The internalization of transmembrane receptors from the cell surface plays a central role in signal regulation. A large body of literature has shown that receptor internalization can occur through different routes[1]; however, because of the difficulty in selectively blocking these routes in vivo, their roles in signaling are poorly understood. Here we investigate this question using null mutations in Drosophila Dynamin, Clathrin, and AP-2 adaptor subunits to analyze internalization requirements for the Delta ligand and its receptor Notch. Bulk Notch is internalized via AP-2-dependent endocytosis, but signaling by Notch requires AP-2-independent Clathrin-dependent endocytosis, highlighting a distinction between Notch endocytic routes required for degradation versus signaling activation. Signaling by the Notch ligand Delta has been shown to require Dynamin, but whether this generates a pulling force of Delta on Notch or allows for Delta entry into a recycling pathway to gain signaling competence is widely debated[2,3]. Surprisingly, we show that signaling by Delta in germline cells can occur by Clathrin-independent endocytosis, when endosomal entry is blocked, and when activity of Rab11 or its effectors is reduced, suggesting that Delta need not pass through a recognized recycling pathway to achieve signaling competence. The absolute requirement for Dynamin-dependent endocytosis but not endosomal entry or Rab11 activity supports ‘pulling force’ rather than ‘recycling’ models for Delta activation.